2011
DOI: 10.1016/j.surg.2011.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Donation after cardiac death: A 29-year experience

Abstract: Objective To report the long-term outcomes of 1218 organs transplanted from donation after cardiac death (DCD) donors from January 1980 through December 2008. Methods One-thousand two-hundred-eighteen organs were transplanted into 1137 recipients from 577 DCD donors. This includes 1038 kidneys (RTX), 87 livers (LTX), 72 pancreas (PTX), and 21 DCD lungs. The outcomes were compared with 3470 RTX, 1157 LTX, 903 PTX, and 409 lung transplants from donors after brain death (DBD). Results Both patient and graft s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 22 publications
4
134
0
3
Order By: Relevance
“…Initial enthusiasm to use these donors has then been tempered due to reported inferior outcomes mostly due to intra-and extra-hepatic biliary complications. Overall national and international outcomes as well as reports from individual programs have extensively documented complications related to utilization of these allografts (16,17). More recent reports have shown that comparable outcomes using DBD and DCD liver allografts can be achieved with appropriate donor and recipient selection as well as paying close attention to surgical technique especially during procurement (10,18).…”
Section: Discussionmentioning
confidence: 99%
“…Initial enthusiasm to use these donors has then been tempered due to reported inferior outcomes mostly due to intra-and extra-hepatic biliary complications. Overall national and international outcomes as well as reports from individual programs have extensively documented complications related to utilization of these allografts (16,17). More recent reports have shown that comparable outcomes using DBD and DCD liver allografts can be achieved with appropriate donor and recipient selection as well as paying close attention to surgical technique especially during procurement (10,18).…”
Section: Discussionmentioning
confidence: 99%
“…cDCDD protocols using the rapid recovery technique and in situ cold perfusion Many cDCDD centers use the rapid recovery technique (RRT) (4,(13)(14)(15) instead of ECMO. W-LST usually occurs in the OR, but it may occur in the ICU.…”
Section: Consentmentioning
confidence: 99%
“…After death declaration, a rapid laparotomy followed by aortic cannulation is performed, with perfusion of cold organ-preservation solution and decompression of the venous system. At other centers, instead of aortic cannulation, femoral vessels are cannulated either premortem (14,15) or postmortem (7), with a double-balloon triple-lumen (DBTL) catheter (7,15). Once death is declared, a cold preservation solution is perfused (in situ cold perfusion [ISP]), and blood is discharged through the femoral vein cannula.…”
Section: Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…Como siempre, la evaluación de cada caso en particular, considerando la mortalidad del paciente en espera, es fundamental para una correcta toma de decisiones 1,6,8 . En otros centros, ya existe amplia experiencia en la donación de órganos después de la muerte o paro cardiaco, pero este tema excede los objetivos de la presente revisión 9,10 .…”
unclassified